2009
DOI: 10.1111/igc.0b013e3181af711e
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolidase Activity and Oxidative Status in Patients With Stage I Endometrial Cancer

Abstract: Increased serum prolidase activity and oxidative stress may be associated with endometrial cancer, and increased serum prolidase activity may be related to local invasion of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…Serum PEPD activity was found to be significantly higher in patients with endometrial cancer than in controls (40). PEPD activity was also shown to be significantly higher in human breast cancer tissues (41) and human lung cancer tissues (42) than in their corresponding control tissues.…”
Section: Discussionmentioning
confidence: 92%
“…Serum PEPD activity was found to be significantly higher in patients with endometrial cancer than in controls (40). PEPD activity was also shown to be significantly higher in human breast cancer tissues (41) and human lung cancer tissues (42) than in their corresponding control tissues.…”
Section: Discussionmentioning
confidence: 92%
“…The final step of collagen degradation is catalyzed by intracellular prolidase; therefore, it may be associated with neoplastic transformation. Increased prolidase activities have been observed in some of cancers, such as lung cancer [15] , breast cancer [16] , endometrial cancer [17] , stomach cancer [18] , renal cell cancer [19] and ovarian cancer [20] . On the other hand, Palka et al [6] showed reduced levels of prolidase in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the higher level of oxidants inside the body or cell may lead to serious consequences, several neurodegerative, parasitic diseases and cancer. [12][13][14]22,23] The imbalance between the levels of oxidants and antioxidants may implicate in the pathogenesis of SCCHN. The basic concept is that the free radicals damage cellular materials which could result in activation or altering normal cells into malignant ones.…”
Section: Discussionmentioning
confidence: 99%